EDEN Research Group: Overview of Bio-regenerative Life Support System research at the German Aerospace Center - Vrakking, Vincent; Philpot, Claudia; Schubert, Daniel; Dorn, Markus; Bunchek, Jess Marie (2024)
The EDEN research group at the German Aerospace Center’s Institute of Space Systems in Bremen, Germany has been investigating bio-regenerative life support systems and Controlled Environment Agriculture technologies since 2011. Long-term human exploration missions to the lunar surface require food supply and reliable life support systems. EDEN focuses on producing fresh food with high nutritional value for the crew and at the same time provide a closed loop bio-regenerative life-support System. A first field test has been conducted in Antarctica as part the EDEN endeavor with the EDEN ISS project and its Mobile Test Facility. The (semi-)closed loop space analogue greenhouse was operated near the German Neumayer Station III in the Antarctic from February 2018 until February 2022. Due to its profound scientific and engineering success, the Mobile Test Facility has returned to Germany and will be refurbished for future operation in Cologne, Germany as part of the DLR / ESA LUNA project. At the same time, a novel Ground Test Demonstrator on global scale is being developed, in collaboration with international partner agencies and commercial companies, to close existing research gaps for future planetary greenhouses and prepare for a potential moon base. This paper provides an overview of the current and planned activities of the EDEN research group on bio-regenerative life support systems, its technical and biological research goals and, specifically, space greenhouses.